2020
DOI: 10.1177/2048872620913849
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of respiratory index in haemodynamically stable patients with acute pulmonary embolism: The Respiratory Index model study

Abstract: Background: Current strategies for prognostic stratification in haemodynamically stable patients with acute pulmonary embolism require improvement. The aims of this study in haemodynamically stable patients with acute pulmonary embolism were (a) to evaluate the prognostic value of a novel respiratory index (oxygen saturation in air to respiratory rate ratio) and (b) to derive a risk model which includes the respiratory index and evaluate its value in predicting 30-day mortality. Methods: Prospective cohorts of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…5 Vedovati and colleagues showed that the use of the respiratory index, the ratio of oxygen saturation in air to respiratory rate, may help to better identify higher-risk patients at risk of imminent decompensation and death. 4 They also confirmed that the observed 30-day mortality rate among patients with (s)PESI=0 was equally low (0.5%) and further minimized (0%) after exclusion of patients with signs of right ventricular dysfunction according to the latest 2019 ESC guidelines. This is in line with the conclusions of a recent systematic review and meta-analysis 7 showing that patients with (s)PESI denoting low-risk or, alternatively, the absence of all Hestia criteria are characterized by very low rates of pulmonary embolism-related complications and early deaths, but that only patients without signs of right ventricular dysfunction were characterized by a rate of complications that was close to zero.…”
supporting
confidence: 56%
See 1 more Smart Citation
“…5 Vedovati and colleagues showed that the use of the respiratory index, the ratio of oxygen saturation in air to respiratory rate, may help to better identify higher-risk patients at risk of imminent decompensation and death. 4 They also confirmed that the observed 30-day mortality rate among patients with (s)PESI=0 was equally low (0.5%) and further minimized (0%) after exclusion of patients with signs of right ventricular dysfunction according to the latest 2019 ESC guidelines. This is in line with the conclusions of a recent systematic review and meta-analysis 7 showing that patients with (s)PESI denoting low-risk or, alternatively, the absence of all Hestia criteria are characterized by very low rates of pulmonary embolism-related complications and early deaths, but that only patients without signs of right ventricular dysfunction were characterized by a rate of complications that was close to zero.…”
supporting
confidence: 56%
“…In this issue of the European Heart Journal -Acute Cardiovascular Care, readers will find four studies contributing valuable information on key risk stratification concepts covering almost the whole spectrum of pulmonary embolism severity. [4][5][6] The low-risk end of the spectrum was addressed by studies that updated or expanded the Pulmonary Embolism Severity Index, the most widely used tool for the identification of potential candidates for home treatment and low-intensity care. Yamashita et al found that patients from the COntemporary ManageMent AND outcomes in patients with Venous ThromboEmbolism (COMMAND VTE) registry with a simplified Pulmonary Embolism Severity Index ((s)PESI) of zero, indicating lowrisk category, had a reasonably low 30-day mortality: two patients out of 383 (0.5%) died due to fatal pulmonary embolism and intracranial haemorrhage, respectively.…”
mentioning
confidence: 99%
“…Second, although this scoring tool was developed using randomized training and validation datasets, external validation is also required. Third, we did not have access to data regarding respiratory rate, cardiac troponin T, and heart type fatty acid binding protein, which precluded comparisons of our tools to the fast prognostic score [12] and respiratory index [6] for predicting adverse outcomes.…”
Section: Limitationsmentioning
confidence: 99%
“…However, it remains important to predict a poor prognosis among normotensive patients with acute PE, as mortality still occurs in this patient population [3][4][5]. Furthermore, the illusion of security at the patient's admission may mask the risk of rapid deterioration and death [6,7]. Unfortunately, there is no universally recognized tool for predicting deterioration and guiding clinical decision-making [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation